Physiognomy and its applications : a study and an annotated translation of Al-Razi's Kitab Al-Firasah - Kaba, Abdulai M. (International Institute of Islamic Thought and Civilization, International Islamic University Malaysia, 2010)
This dissertation attempts to study Razi and his work on physiognomy or firasah. It begins with a historical study of physiognomy from the Ancient to the time of Razi and beyond. In view of this, the dissertation aims ( 1) to justify the need for a critical and an annotated textual translationi contextual analysis, of the two versions of Razi's Kitab al-Firasah to establish his authorship or lack of it over them, (2) to compare his firasah with Aristotle's "Anima" to probe their similarities and differences, (3) to critically analyze Razi' s assumptions and interpretations of firasah in the light of the advances made in the various related sciences, ( 4) to examine the position of physiognomy in the scheme of knowledge, and (5) to assess its reliability and continued validity. The research also contributes the first English translation of Kitab al-Firasah from the original Arabic version. In translating the text the researcher has endeavored to capture the spirit of the original contents without compromising the text to accommodate the various semantic and linguistic nuances that may differ between both these languages.